Application simulator automated workplaces driller SHELF 6000 DRILL in educational process on forward 131000 «Oil and Gas Engineering» - A V Sinchenko; I L Kapitonova (RUDN Journal of Engineering Research, 2014)
The article presents the results of development simulator workstation driller SHELF 6000 Drill. 2 exercises described «Rotary drilling with extraction of the core» and «cementing». Conclusions about the use of the simulator in the educational process in the direction 131000 «Oil and gas engineering».